MOVE Mobile One-time Password Version E - Blanco, Mae Sincere S.
In today's generation, the wide use of username-password schemes for authentication has been quite an issue in protecting vital information of the user. One's identity can be easily stolen one other people gain access to a user's account. Identity theft lead to serious damage and property lost. In order to compensate for the weakness of passwords, there is a need to use a more secure approach for authentication. Although One-Time-Passwords (OTP) can already improve authentication, there is still a need to enhance the algorithm in order to resist more attacks without sacrificing efficiency and user convenience. This research improves the usual One-Time-Password generation by integrating challenge-response schemes with mobile phones.